Spatio-temporal patterns of rice submergence in north-eastern Thailand with TERRA-MODIS - Chemin, Yann H.; Phupak, S. (2012)
Rice submergence is the condition by which the water level rises above the rice crop canopy. In general,rice plant response to submergence is to elongate its shoots above the rising water level. This costs in energy andeventually has a direct impact in terms of reducing yields. A specific gene, called Sub1, when introgressed intopopular rice varieties by Marker Assisted Back-crossing, nearly stops the natural elongation process and permits agiven local rice variety to sustain submerged conditions for a generally recognized period of about 2 weeks. Plantbreeders now look for well-identified and location-accurate submergence areas in order to disseminate suchimproved local rice varieties. Remote sensing is proposed to provide surface water maps at high temporalresolution, determining a percentage of occurrences of surface water for a given pixel. Occurrence is defined as thecount of days of identified surface water within a given period, returned in a percentage on that period. Rice areamaps and knowledge of crop calendars are proposed to add to the assessment of submergence prone areas in theNortheastern Thailand.